The Influence of Yttrium Doping on The Microstructure and Magnetic Properties of Barium Hexaferrite - Nasution, Nazaruddin; Humaidi, Syahrul; Frida, Erna; Na Duma, Tulus; Zhemas Zul Nehan, Phahul; Naibaho, Marzuki; Ginting, Masno (Trends in Sciences, 2025)
This study investigates the effect of Yttrium (Y) addition as a doping element on the microstructure and magnetic properties of barium hexaferrite (BaFe12O19), synthesized using the High Energy Milling (HEM) method. Samples with varying Y concentrations (x = 0.00, 0.05, 0.1 and 0.15) were prepared and characterized using X-ray Diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX), and Vibrating Sample Magnetometer (VSM). The XRD results showed that all samples exhibited a hexagonal M-type crystal structure with a P63/mmc space group. The addition of Y caused a shift in diffraction peaks toward lower angles, indicating an increase in lattice parameters. SEM morphological analysis revealed a decrease in grain size (DSEM) with increasing Y content, from 813 nm (x = 0) to 519 nm (x = 0.15). Additionally, magnetic measurements indicated that the sample with x = 0.05 (Y5) had the optimal magnetic properties, with a saturation magnetization (MS) of 58.11 emu/g and a coercivity (HC) of 2,715 Oe, making it a promising candidate for microwave absorber applications. This study demonstrates that Y doping can modify the structure and enhance the magnetic properties of barium hexaferrite, particularly in optimizing magnetization and reducing coercivity for microwave absorption applications. HIGHLIGHTS BaFe12−xYxO19 (x =0, 0.05, 0.1 and 0.15) synthesized using the solid-state reaction method with High Energy Milling (HEM). XRD confirmed single-phase M-type hexaferrite structure. Yttrium doping increased lattice parameters and reduced grain size. Optimal composition (x = 0.05) achieved Ms = 58.11 emu/g and Hc = 2,715 Oe. Enhanced magnetic properties suitable for microwave absorber applications. GRAPHICAL ABSTRACT